Influence of spray volumes, nozzle types and adjuvants on the control of phoma coffee rust - Santinato, Felipe; Ruas, Renato Adriane Alves; Tavares, Tiago de Oliveira; Silva, Rouverson Pereira da; Godoy, Mateus Altarugio (Coffee Science - ISSN 1984-3909, 2017)
Pesticides are often applied under incorrect conditions such as inappropriate nozzles types and high spray volumes. Such errors result in spray drift and run off, causing inefficiency on the control of pests and diseases, beyond environmental contamination. Here we evaluate the influence of spray volumes, nozzle types and adjuvants on the control of phoma and coffee rust. The objective in this work was to evaluate the feasibility of reducing the volume of syrup in the absence and presence of adjuvant, using three spray nozzle types, analyzing the uniformity of the spray distribution to thirds of the plant and its penetration and effectiveness of phytosanitary products. The treatments were t arranged in a factorial 3 x 2 x 2 + 1, outlined in a randomized block design with three replications in a split plot. Treatments were three-pointed on type empty cone (ATR Amarela; JA Preto e Disc-Core AD2AC23), two spray volumes (300 and 500 L ha-1), on absence and presence of adjuvant (TRUMP), and a control (experiment without disease control). It was concluded that the volume of spray liquid can be reduced to 300 L ha-1, without harming the quality of spraying and disease control. The adjuvant has not brought any benefits for the application, and the most suitable spray nozzle is the ATR Amarela.